Structural aspects of railway truss bridges affecting transverse shear forces in steel-concrete composite decks = Konstrukcyjne aspekty kolejowych mostów kratownicowych decydujące o poprzecznych siłach rozwarstwiających w pomostach zespolonych - Siekierski, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At the steel-concrete interface, the horizontal shear forces that are transverse to cross beams occur due to joint action of the steel-concrete composite deck and the truss girders. Numerical analysis showed that values of the forces are big in comparison to the longitudinal shear forces. In both cases extreme force values occur near side edges of a slab.
Keywords: pomost zespolony; siły ścinające; most kratownicowy; most kolejowy; composite deck; shear force; truss bridge span